Implementasi Website E-Commerce untuk Meningkatkan Penjualan Toko Kelontong di Era Digital : Studi Kasus: Toko Kelontong Ibu Soimah - Wakhlul Azmi; Anisa Lutfiyani (Jurnal Teknik Informatika dan Teknologi Informasi, 2026)
The rapid advancement of information technology in the digital era has encouraged Micro, Small, and Medium Enterprises (MSMEs) to adopt internet-based sales systems to improve operational efficiency and business competitiveness. Toko Kelontong Ibu Soimah continues to face several operational challenges, including manual sales processes, unstructured transaction records, and marketing activities limited to the surrounding neighborhood. This study aims to implement an e-commerce website as an online sales platform and evaluate its impact on improving the store's sales performance. The system was developed using the Prototype method, consisting of five stages: Communication, Quick Plan, Modeling Quick Design, Construction of Prototype, and Deployment, Delivery & Feedback. The application was developed using PHP with the Laravel framework and MySQL as the database management system. System functionality was evaluated through Black Box Testing, while user acceptance was measured using User Acceptance Testing (UAT) with a Likert scale. The testing results indicated that all major system features functioned properly without significant errors. The UAT produced an average score of 4.4, categorized as "Very Good," indicating that the system is user-friendly and meets operational requirements. The implementation of the e-commerce website generated significant positive outcomes, increasing weekly transactions by 75% (from 20 to 35 transactions) and sales revenue by 75% (from IDR 2,000,000 to IDR 3,500,000). These findings demonstrate that the e-commerce website effectively expands market reach, improves operational efficiency, and enhances sales performance at Toko Kelontong Ibu Soimah.